Factors and Predictors of Health Related Quality of Life of the General Population of Pakistan - Nasim, Aqeel; Haq, Noman Ul; Riaz, Sohail; Khan, Sumaira Irum; Khuda, Fazli; Sipra, Muhammad Faraz; Tariq, Bazil; Tahir, Maria; Saood, Muhammad; Yasmin, Riffat; Manzoor, Kiran; Zeeshan Danish, Muhammad (Frontiers in Public Health, 2022)
Background and Objective: The standards of living, betterment in public health, and medical care in Pakistan are increasing day by day, health-related quality of life (HRQoL) has been increasingly acknowledged in various patient's reported outcomes in Pakistan. However, a large-scale general population-based study on assessing HQRoL in Pakistan was not conducted. Therefore this study aimed to evaluate HRQoL for the general Pakistani population. Material and Methods: A cross-sectional study with a population sample (n = 16672) was selected from all Pakistan provinces using a stratified sampling approach. The EQ-5D-3L tool was used to measure the HRQoL of the general population of Pakistan. The descriptive and inferential statistics have been done by using SPSS version 20. Results: Overall, 121 health states were reported. EQ-5D index score and EQ-VAS scores were 0.74 ± 0.32 and 0.75 ± 0.25, respectively. The percentage of people responding to any problems increased with age. Males have better health as compared to females in all age groups. All demographics were significantly associated (P<0.01) with the mean EQ5D score and VAS except residence (p>0.05). The regression model reported that age was the best predictor of the EQ-5D index after adjusting for the covariates (beta=0.19; p<0.001). This study provides Pakistani population HRQoL data measured by the EQ-5D tool, based on a national representative sample. Conclusion: The current study concluded that population norms help make Pakistan's general persons' health status. Socioeconomically deprived groups have inferior health status than more advantaged. The trends detected in high-income nations were usually similar to Pakistan.